Trade policy options for the Asia-Pacific Region in the 1990's : the potential of open regionalism. - Elek, Andrew (1992)
Lists factors that impede or distort international transactions in the Asia-Pacific region. Points out that the benefits of further liberalization would accrue to the region itself.